Information Seeking related to the Congregational Worship in Pandemic Covid-19 : Between Conventional Media and Social Media - Prastya, Narayana Mahendra Prastya; Ningsih, Ida NDK (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2022)
The Indonesian government had issued a regulation that restricted the implementation of congregational worship during the Covid-19 pandemic to prevent the transmission of the virus. However, not all people comply with these government regulations. Information become one factor that influence a person's behavior. This study aims to find out how the Indonesian Muslim community uses the media to obtain information related to the implementation of worship during the Covid-19 pandemic. The reason for choosing the Muslim community is because as the majority people in Indonesia and there are a number of congregational worships performed by Muslim. This study uses a quantitative method by conducting a survey of respondents aged between 18-55 years. Online questionnaires were distributed to respondents in the period September 2021 – October 2021. After the validity and reliability tests, there were 92 answers which would then be processed. The results showed that the majority of respondents were in the age range between 18-37 years (a 73 percent) and the majority (65 percent) stated that they joined certain religious organizations. Social media is widely accessed because of the ease of access to information, relevance of information, usefulness, and updating of information. The majority of respondents (78 percent) use social media as their main source of information seeking. There are also conventional mass media, official media belonging to organizations, and official media from religious organizations are rarely used. Access to information is a factor why social media is widely chosen. Even so, respondents still put their trust in conventional mass media thanks to the accuracy of the information and the credibility of the media.